Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.molmet.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic growth hormone receptor (GHR) controls hepatic glucose production in nutrient-sensing leptin receptor (LepRb) expressing neurons

Abstract: ObjectiveThe GH/IGF-1 axis has important roles in growth and metabolism. GH and GH receptor (GHR) are active in the central nervous system (CNS) and are crucial in regulating several aspects of metabolism. In the hypothalamus, there is a high abundance of GH-responsive cells, but the role of GH signaling in hypothalamic neurons is unknown. Previous work has demonstrated that the Ghr gene is highly expressed in LepRb neurons. Given that leptin is a key regulator of energy balance by acting on leptin receptor (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 82 publications
(96 reference statements)
5
40
0
2
Order By: Relevance
“…However, LepR GHR KO mice utilized less glucose during a hyperinsulinemiceuglycemic clamp (Fig. 2H), confirming previous findings by Cady et al (21) showing insulin resistance after GHR ablation in LepR cells. We next performed an insulin tolerance test (ITT) to determine the capacity of the animals to recover from insulin-mediated hypoglycemia.…”
Section: Ablation Of Ghr In Lepr-expressing Neuronssupporting
confidence: 90%
See 3 more Smart Citations
“…However, LepR GHR KO mice utilized less glucose during a hyperinsulinemiceuglycemic clamp (Fig. 2H), confirming previous findings by Cady et al (21) showing insulin resistance after GHR ablation in LepR cells. We next performed an insulin tolerance test (ITT) to determine the capacity of the animals to recover from insulin-mediated hypoglycemia.…”
Section: Ablation Of Ghr In Lepr-expressing Neuronssupporting
confidence: 90%
“…However, it is not known how GH secretion pattern affects the activity of GH-responsive neurons. Recent studies investigated the metabolic phenotype of mice deficient in GHR in LepR cells (21,22). These studies found that LepR GHR KO mice have normal food intake and body weight, but they present hepatic insulin resistance (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, quantitative PCR and immune-histochemical studies confirmed a near ubiquitous expression of GHR throughout the brain of humans as well as rats and mice (reviewed in (253,254,255)). Particularly high expression levels of GHR was observed in the choroid plexus, pituitary, hippocampus, thalamus, and hypothalamus (256). It was further observed that GH-binding in brain tissue decrease as a function of age (257) along with age related decline in GH production as well as cognition and memory (258).…”
Section: Ghr Presence In Brainmentioning
confidence: 99%